A SURVEY ON KNOWLEDGE AND ATTITUDE ABOUT ENDODONTIC MISHAPS AND ITS MANAGEMENT AMONG POSTGRADUATE STUDENTS (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Endodontic treatment includes procedures that were framed to maintain the health of pulp tissue and a periapical portion of the tooth. If the pulp is diseased or injured, the treatment is done to preserve the normal radicular tissues. This study aims to determine the knowledge, attitude, and practice about endodontic mishaps and their management among practicing dentists. Materials and Methods: A questionnaire consisting of 13 multiple choice questions was prepared based on etiology, prevention, and management of endodontic mishaps using online software. This study was conducted online which included 101 participants who were general practitioners and specialists working in clinics. The data were collected and analyzed using SPSS software.Results: The result shows that only 59% of surveyed dentists are aware of etiology, 58.8% were aware of prevention,and 51.6% aware of the management of endodontic mishaps that occur during the procedure. P value was not significant (p>0.05)Conclusion: Dentists, being members of the health-care profession, should know about endodontic mishaps and their management which may occur during the procedure. Only 56.4% are aware of endodontic mishaps and their management according to the study.